The Stereotactic Intracerebral Hemorrhage Underwater Blood Aspiration (SCUBA) technique for minimally invasive endoscopic intracerebral hemorrhage evacuation. (23rd March 2018) - Kellner, Christopher Paul; Chartrain, Alexander G; Nistal, Dominic A; Scaggiante, Jacopo; Hom, Danny; Ghatan, Saadi; Bederson, Joshua B; Mocco, J
Abstract : Background: Endoscopic intracerebral hemorrhage (ICH) evacuation techniques have gained interest as a potential therapeutic option. However, the instrumentation and techniques employed are still being refined to optimize hemostasis and evacuation efficiency. Objective: We describe the application of a specific endoscopic technique in the treatment of ICH called the Stereotactic Intracerebral Hemorrhage Underwater Blood Aspiration (SCUBA) technique. It differs from previously described minimally invasive ICH interventions in that it combines two separate neuroendoscopic strategies in two phases, the first under dry-field conditions and the second using a wet-field strategy. Methods: All patients who underwent endoscopic ICH evacuation with the SCUBA technique from December 2015 to September 2017 were included. Results: The SCUBA technique was performed in 47 patients. The average evacuation percentage was 88.2% (SD 20.8). Active bleeding identified to derive from a specific source was observed in 23 (48.9%) cases. Active bleeding was addressed with irrigation alone in five cases (10.6%) and required electrocautery in 18 cases (38.3%). Intraoperative bleeding occurred in 3 patients (6.4%) and postoperative bleeding occurred in a single case (2.1%). Conclusions: The SCUBA technique provides surgeons with a defined strategy for true endoscopic hematoma evacuation. In particular, the fluid-filled cavity in SCUBA Phase 2 has the potential to provide several advantages over the traditional air-filled strategy, including clear identification and cauterization of bleeding vessels and visualization of residual clot burden. Further investigation is necessary to compare this technique to others that are currently used.